Empowering youth in internally displaced persons camps through the role of non-governmental organisations at Borno State, North Eastern Nigeria - Sadat, Shehu (2022)
The number of Youth in the Internally Displaced Persons (IDPs) camp in Borno state that are in need of empowerment and support is alarming. The insecurity instigated by the Boko Haram terrorist in Nigeria precisely the North-eastern Nigeria is not only disturbing, demoralizing and frightening, it has led to unrest and life of uncertainty amongst the youth especially Borno state who have found themselves in IDPs camps. Among the problems faced by the youth in IDPs camps in Borno state is the issue of empowerment which the Non-governmental Organizations (NGOs) has taken upon themselves. This study therefore sought to investigate not only the reasons for the continuous increase in number of the internal displacement person in Borno State camps, but the place of NGOs in the empowerment of youth in Borno State IDPs camps, as well as the setback hindering the activities of these NGOs in their quest for Youth Empowerment in Borno State IDPs camps, and the measures that can be used by the NGOs toward ensuring adequate Youth Empowerment in Borno State IDPs camps. Qualitative case study approach and purposive sampling was used in the selection of 24 key informants which were drawn from the concern stake holders with the necessary experiences and knowledge. Thematic analysis was used to analyze the data. The finding of the study shows that the factors responsible for upsurge in IDPs in Borno state communities are the activities Boko Haram insurgency, armed banditry and violence attacks from the insurgent. Furthermore, the NGOs have played a significant role in youth empowerment in Borno state IDPs through technical assistance, provision of financial support, provision of awareness, mobilization and importantly, entrepreneurship training as well as provision of small businesses. However, the NGOs are faced with a number of challenges which include financial difficulties, limited resource, volatile security situation in the state and the lack of co-operation. Interestingly, the study found that strategies have been adopted by the NGOs towards adequate youth empowerment in Borno state, among the strategies are financial assistance, provision of business loan, and involvement of all stakeholders. Thus, conclude that the NGOs are significant partners in the business of youth empowerment in Borno state IDPs camp.